Unexpected Ca2+-mobilization of oxaliplatin via H1 histamine receptors. (March 2020) - Potenzieri, A; Riva, B; Genazzani, AA
Highlights: Oxaliplatin induces Ca 2+ -signals in dorsal root ganglia by activating H1 histamine receptors. Activation of H1 receptors leads to TRPV1 channel opening in DRG neurons. Activation of H1 receptors may be linked to hypersensitivity reactions and itch. Graphical abstract: Abstract: Oxaliplatin is a widely used chemotherapeutic drug and represents the cornerstone of colorectal cancer therapy, in combination with 5-fluorouracil and folinic acid. As with many chemotherapeutic agents, its use is associated with a number of side effects, ranging from hypersensitivity reactions to haematological dyscrasias. Oxaliplatin also induces acute and chronic peripheral neuropathy. While it is likely that the haematological side effects are associated with its anti-proliferative effects and with the ability to form DNA adducts, the molecular mechanisms underlying peripheral neuropathy and hypersensitivity reactions are poorly understood, and therefore the choice of adequate supportive therapies is largely empirical. Here we show that an acute low dose oxaliplatin application on DRG neurons is able to induce an increase in intracellular calcium that is dependent on the Histamine 1 receptor (H1). Oxaliplatin-induced intracellular calcium rises are blocked by two selective H1 antagonist, as well as by U73122, a PLC inhibitor, and by 2-APB, a non-specific IP3 receptor blocker. Moreover, expression of the H1 receptor on HEK293 t cells unmasks an oxaliplatin-induced Ca 2+ -rise. Last, activation of H1 via either histamine or oxaliplatin activates TRPV1 receptors, a mechanism that has been associated with itch. These data, together with literature data that has shown that anti-histamine agents reduce the incidence of oxaliplatin-induced hypersensitivity, may provide a molecular mechanism of this side effect in oncological patients.